1989
DOI: 10.1104/pp.89.4.1247
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinin Production by Bradyrhizobium japonicum

Abstract: Although there is considerable circumstantial evidence for the involvement of cytokinins in legume nodulation, the cytokinins produced by rhizobia have not been well characterized. Bradyrhizobhum Japoncum 61A68, a bacterium which nodulates soybean (Glycine max [L.] Meff.), was grown in defined medium.Cytokinins were purified from the culture medium by Amberlite XAD-2 chromatography and fractionated by column chromatography on Sephadex LH-20 in 35% ethanol. Pooled fractions from the Sephadex column were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(30 citation statements)
references
References 31 publications
0
29
0
1
Order By: Relevance
“…5), and 17 Ϯ 7 ng/mg of tRNA was recovered from Arabidopsis PPFM isolates (data not shown). These values are much lower than the 200 ng/mg reported for B. japonicum (40), but the recovery procedures differed; using our procedures, we recovered less than one-half of the previously reported levels of trans-zeatin riboside from B. japonicum tRNA (data not shown). No significant signal corresponding to the cis isomer was obtained, as shown by the lack of active fractions in an RIA for the cis isomer (Fig.…”
Section: Incorporation Of [ 3 H]adenine Into Cytokinins By Ppfmsmentioning
confidence: 44%
See 1 more Smart Citation
“…5), and 17 Ϯ 7 ng/mg of tRNA was recovered from Arabidopsis PPFM isolates (data not shown). These values are much lower than the 200 ng/mg reported for B. japonicum (40), but the recovery procedures differed; using our procedures, we recovered less than one-half of the previously reported levels of trans-zeatin riboside from B. japonicum tRNA (data not shown). No significant signal corresponding to the cis isomer was obtained, as shown by the lack of active fractions in an RIA for the cis isomer (Fig.…”
Section: Incorporation Of [ 3 H]adenine Into Cytokinins By Ppfmsmentioning
confidence: 44%
“…Because of the difference in stereoisom-erism between the two paths of cytokinin biosynthesis, it has been assumed that tRNA turnover makes a minor contribution, at best, to the plant cytokinin pool. However, trans-hydroxylated zeatin has been found in the tRNAs and culture filtrates of Bradyrhizobium japonicum (40) and the rhizosphere bacterium Azotobacter vinlandii (1,43). The trans isomer in the tRNA of Agrobacterium that was described by Chapman and Morris (6) was later shown by workers in the same laboratory to be the cis isomer (32).…”
mentioning
confidence: 99%
“…An additional level of complexity is added by the perturbation of hormone levels in nodules, which can be in response to. or even mediated by, the microsymbiont (Sturtevant and Taller, 1989), and which can also affect the expression of plant defence response genes (Robinette and Matthysse. 1990;Dominov et al, 1992).…”
Section: (8) Inhibition Of Nodulation By Nitrate and Lightmentioning
confidence: 99%
“…Furthermore, Maxwell et al (1993) reported that isoflavonoid biosynthesis is higher than, and uncoupled from, nod-on synthesis in Medicago nodules, implying that either nod-offs (or, at a later stage, phytoalexins) are being produced. An additional level of complexity is added by the perturbation of hormone levels in nodules, which can be in response to, or even mediated by, the microsymbiont (Sturtevant and Taller, 1989), and which can also affect the expression of plant defence response genes (Robinette and Matthysse, 1990;Dominov et al, 1992).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…A/-Acetylglutamic acid induces nodulelike primordia on clover (Philip-Hollingsworth et al, 1991), whereas diglycosyldiacylglyceride causes uniform cell division in the cortex, leading to a thick and short root phenotype (F. Dazzo, personal communication). Rhizobia are also known to secrete cytokinins (Sturtevant and Taller, 1989). These compounds apparently have distinct receptors and use separate signal transduction pathways that may converge to elaborate their responses via a common route.…”
Section: Early Signal Exchange(s) Between Plant and Bacteriamentioning
confidence: 99%